Visually optimized light field 3D display using multi-layer LCDs - Feng, Yuxian (2017)
Multi-layer light eld 3D display is a kind of computational 3D display which gains increasing interests for its holographic-like e ect and compatibility with 2D displays. However, two major shortcomings, depth limitation and multi-layer blur, are not fully addressed in the traditional light eld modeling and reconstruction based on liquid crystal displays (LCDs). Considering these two disadvantages, we propose a depth guided and blur dependent optimization method for multi-layer light eld display. Di erent from previous cascaded light eld displays, which only use the xed initialization plane as the depth center of display content, the proposed method automatically chooses the best depth initialization from three di erent classical con gurations by introducing the duality properties between light eld capture and multi-layer light eld displays. Experiments demonstrate that the proposed method provides a promising advantage in visual perception of compressive light eld displays with both software simulation and prototype demonstration. The main contribution is to optimize the display based on the con gurations of light eld capture and its e ect on displayed image quality rather than focusing on the display itself.